The Role of Design in Successful Flipping: How to Increase the Value of Real Estate (International Journal of Scientific Research and Management (IJSRM), 2025)
The strategic importance of design in real estate flipping has evolved into a vital element that determines both property value appreciation and investment success and market leadership. The research investigates the impact of interior and architectural design modifications on the increased resale value of flipped properties. The research investigates the relationship between design elements such as aesthetics and functionality and technology and their impact on real estate investment profitability through a review of 26 recent peer-reviewed publications. The research analyzed home staging and renovation innovation and modern spatial organizing effects on customer behavior and selling rates through qualitative perception and quantitative performance data. The research combines sustainability principles with digital design tools and investment behavioral indicators to develop an inclusive framework for design-led flipping success. The research demonstrates that high-quality design enhances property attractiveness while fulfilling modern consumer needs and regulatory requirements which directly boosts investment returns. The study findings provide real estate developers and home investors and designers with essential knowledge to enhance their home transformation processes in volatile housing markets.